Overcoming dormancy in seeds of Dietes bicolor (Steud.) Sweet ex Klatt - Borges,Thiago Roberto Rezende (2022)
Abstract Seminiferous propagation of Dietes bicolor is hindered by the probable physical and/or morphophysiological dormancy. The objective was to analyze the efficacy of different methods of overcoming dormancy in D. bicolor seeds to determine a possible pre-germination treatment for the species. Two experiments were conducted: (I) Evaluation of the breaking of physical dormancy, in which the treatments of mechanical scarification were carried using sandpaper #100; chemical scarification with sulfuric acid (H2SO4) for 5 and 10 minutes and immersion in hot water (70 ºC), also, for 5 and 10 minutes, were evaluated. The intact seed was considered a control. (II) Evaluation of morphophysiological dormancy, in which the seeds were submitted to combined treatments of stratification of hot temperature (20-35 °C) and/or cold temperature (9 ºC), distributed in periods of 0, 1, and 2 weeks, totalizing 9 treatments. In both experiments, germination percentage (G), germination speed index (GSI), and first count (FC) were determined, using a randomized block design, and evaluated by the Scott-Knott test at 1% and Dunnett’s test at 5%. The use of H2SO4 10 minutes induced 42% germination, 0.52 GSI, and 18% FC, but only FC was significantly different from the control. In the second trial, the treatment that spent only two weeks in hot temperatures (20-35 ºC) showed the highest germination (30%), compared to the control (G = 22%). These results provide relevant information for understanding the physiology of D. bicolor germination, in addition to contributing to the optimization of pre-germination practices for this important ornamental species.